E-learning as a Tool for Human Resource Development. Case ABB - Metsä-Heikkilä, Katri (My University, 2008)
The rapid change of knowledge-intensive and technology-oriented working life requires continuous development. At the same time, new technology can be seen as an enabling factor in finding solutions to this challenge. One potential tool for human resource development is e-learning, credit-granting education or training courses delivered via audio, video, or computer technologies such as the Internet. Many organizations have taken e-learning methods in use, or are interested in using e-learning in their organizations. One of the most obvious benefits of e-learning is the tremendous cost-saving because there will be no travel costs or lost working hours. However, e-learning is sometimes interpreted in a narrow sense as referring to process of delivering digital information and study materials to users through electronic media. Oversimplifying the notions of knowledge and learning can easily lead to misunderstandings and disappointments. At their best, e-learning environments have the potential to support cognitive, social, motivational, and affective processes of learning. This study aims to find out how to build an effective e-learning environment. It is done by reviewing the literature of pedagogical aspects of workplace learning in general and e-learning in particular. As e-learning in the workplace always is concerned with adult learning, adult learning theories should form the basis for the design of e-learning environment in the workplace. The creation of motivating, flexible and diverse multimedia technology represents important challenge in building effective e-learning environments. The study draws a categorization for critical phases of designing and implementing e-learning effectively. The interviews are carried out to find evidence of importance of the four phases of designing and implementing e-learning. The total amount of respondents was 14, out of which ten via e-mail and four face-to-face. The results of the study indicate that all four phases are needed in designing and implementing e-learning effectively. The case company succeeded in two phases out of four, but many weaknesses (such as lack of interactivity) were reported in the interviews.
Keywords: e-learning; learning; fi=Johtaminen ja organisaatiot|en=Management and Organization|